Annual Plan 1980-81 Orissa (Draft) - Planning Commission (Planning Commission, 1980)
The experience of more than a quarter century of planned efforts for economic development and social change has shown broadly two things, viz; (i) the pace of development has been too inadequate and often too unstable and (ii) that the benefits of development have gone largely in favour of the richer class, while the low-end poverty and unemployment continue to affect the weaker sections. It is noticed that while growth rates of the economy over the plan periods are nearly stagnant at a relatively low level, the annual growth rates are extremely fluctuating. According to the latest appraisal of the economy by the National Council of Applied Economic Research, in the first four Five Year Plans, the actual percentages of growth in the country were 3.8, 3.7, 3.2 and 3.5 respectively and in the Fifth Plan, the rate was 3.3 percent. Annual growth rates measured by G. N. P.
Government of Orissa